PERSPEKTIF PSIKOLOGI PEMBELAJARAN TERHADAP PEMANFAATAN INTERNET - Syarwan Ahmad (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2011)
This article explains theories and thought of Psychology of Learning which support the idea of using Information Computer Technology in instructional program. It focuses on the rational of applying ICT and the role of E-mail, mailing list, website and mind-tools to improve learning program. In conclusion, the implementation of ICT, especially Internet, is really relevant to theories and new trend in the field of Psychology of Learning called constructivism. Email, mailing list, website and computer mind-tools improve instructional program. Therefore, ICT especially Internet is necessary to be inserted in all aspects of curriculum.